Peningkatan Kemampuan Membaca Memahami Teks Bahasa Jerman dengan Teknik Skimming dan Scanning - Sorean, Rosma Kurnia; Saud, Syukur; Rijal, Syamsu (Universitas Negeri Makassar, 2025)
Abstract. This research is a classroom action research which consists of two cycles. This research aims to determine the planning, implementation and results of improving the ability to read and understand German texts through Skimming and Scanning techniques. This research is classroom action research which consists of two cycles with each cycle consisting of planning, implementation, observation and reflection stages. Research data consists of two types, namely qualitative data and quantitative data. Qualitative data was obtained from teacher and student observations, while quantitative data was obtained from the results of reading ability tests to understand German texts in cycle I and cycle II. The average score for the ability to read and understand German text for class German studentsKeywords: : Learning Techniques, Reading Ability, Skimming and Scanning Techniques